2016
DOI: 10.1186/s13023-016-0519-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wnt and Notch signaling: a clue to the renal disease in Schimke immuno-osseous dysplasia?

Abstract: BackgroundSchimke immuno-osseous dysplasia (SIOD) is a multisystemic disorder caused by biallelic mutations in the SWI/SNF-related matrix-associated actin-dependent regulator of chromatin, subfamily A-like 1 (SMARCAL1) gene. Changes in gene expression underlie the arteriosclerosis and T-cell immunodeficiency of SIOD; therefore, we hypothesized that SMARCAL1 deficiency causes the focal segmental glomerulosclerosis (FSGS) of SIOD by altering renal gene expression. We tested this hypothesis by gene expression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…These findings are consistent with previous reports demonstrating podocyte Notch activation in chemically induced models of glomerulosclerosis and in human biopsies of glomerular disease. 28 , 36 , 37 , 38 Increased podocyte Hes1 , Hes3 , Hes5 and Hey1 , Hey2, and HeyL have been found in streptozotocin- and puromycin aminonucleoside–induced glomerulosclerosis. 28 Podocyte apoptosis has been shown to play an instigating role in the pathogenesis of FSGS, and Notch activation in mature podocytes induces apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with previous reports demonstrating podocyte Notch activation in chemically induced models of glomerulosclerosis and in human biopsies of glomerular disease. 28 , 36 , 37 , 38 Increased podocyte Hes1 , Hes3 , Hes5 and Hey1 , Hey2, and HeyL have been found in streptozotocin- and puromycin aminonucleoside–induced glomerulosclerosis. 28 Podocyte apoptosis has been shown to play an instigating role in the pathogenesis of FSGS, and Notch activation in mature podocytes induces apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Observations in SIOD patient tissues have shown that a trait of interest can arise from either increased or decreased expression of key genes in tissues of SIOD patients. 7,20,21 Some gene expression changes appear to arise from effects of SMARCAL1 activity at promoters, 53 whereas others might arise from epigenetic changes induced by replication stress. Future genome-wide studies to assess the relationship between chromatin structure as well as epigenetic marks and gene expression will provide valuable insight into the mechanism by which SMAR-CAL1 deficiency alters gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila Marcal1 and human SMARCAL1 overexpression screen was carried out at 28 C and has been previously described. 14,21 Drosophila have 5 longitudinal veins (L1, L2, L3, L4, and L5) as well as an anterior and posterior cross vein (ACV and PCV); overexpression of Marcal1 and SMARCAL1 leads to an ectopic vein parallel and anterior to L2, an ectopic vein extending laterally from the PCV, a partially missing or completely absent ACV or PCV, and distal bending or splitting of longitudinal veins L2, L4, and L5. 14,21 We screened for trxG and PcG alleles that lead to the suppression or enhancement of the ectopic wing veins induced by the overexpression of Marcal1 and SMARCAL1.…”
Section: Drosophila Genetic Studiesmentioning
confidence: 99%
See 2 more Smart Citations